Immune Mechanisms in Cardiovascular Diseases Associated With Viral Infection - Gopal, Radha; Marinelli, Michael A.; Alcorn, John F. (Frontiers in Immunology, 2020)
Influenza virus infection causes 3–5 million cases of severe illness and 250,000–500,000 deaths worldwide annually. Although pneumonia is the most common complication associated with influenza, there are several reports demonstrating increased risk for cardiovascular diseases. Several clinical case reports, as well as both prospective and retrospective studies, have shown that influenza can trigger cardiovascular events including myocardial infarction (MI), myocarditis, ventricular arrhythmia, and heart failure. A recent study has demonstrated that influenza-infected patients are at highest risk of having MI during the first seven days of diagnosis. Influenza virus infection induces a variety of pro-inflammatory cytokines and chemokines and recruitment of immune cells as part of the host immune response. Understanding the cellular and molecular mechanisms involved in influenza-associated cardiovascular diseases will help to improve treatment plans. This review discusses the direct and indirect effects of influenza virus infection on triggering cardiovascular events. Further, we discussed the similarities and differences in epidemiological and pathogenic mechanisms involved in cardiovascular events associated with coronavirus disease 2019 (COVID-19) compared to influenza infection.